A Review of Research on Blockchain Consensus Algorithms - Jiayi Wang, Zhigang Zhang; Wang, Jinlong (Procedia computer science, 2025)
The core of blockchain technology, as a decentralized distributed ledger technology, lies in how to reach consensus without a centralized institution. Consensus algorithm is the cornerstone of blockchain, which determines the security, performance and decentralization degree of blockchain. This paper starts from the basic concept of blockchain consensus algorithms, analyzes the working principle, advantages and disadvantages, and application scenarios of current mainstream consensus algorithms, and discusses the future development trend of consensus algorithms.